2006
DOI: 10.2136/vzj2005.0138
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Metal Leaching from a Poultry Litter–Amended Udult under Pasture Vegetation

Abstract: More than 1 billion broiler chickens (Gallus gallus domesticus) are produced annually in Arkansas, with nearly 900 Gg of waste (i.e., litter) generated. Poultry litter is typically land applied as a means of disposal to nearby pastures as an organic fertilizer. Aside from essential plant nutrients, poultry litter also contains heavy metals, yet little is known about the potential of these metals to leach from soils with a history of litter application. The objective of this study was to continuously monitor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(80 citation statements)
references
References 23 publications
7
73
0
Order By: Relevance
“…Research was initiated in 2002 at the Agricultural Research and Extension Center in Fayetteville, AR (36°05′49.18′′ N, 94°10′44.65′′ W; elevation, 394.7 m) (Pirani et al, 2006) in an area mapped as a Captina silt loam (fine‐silty, siliceous, active, mesic Typic Fragiudult) (USDA‐NRCS, 2013). Each of six field plots (6‐m long by 1.5‐m wide) had a 5% west‐to‐east slope, had a history of land‐applied BL before 2002, and was initially chosen based on similar soil pH (6.2 ± 0.5 [SE]) and high Mehlich‐3–extractable P (210 ± 24 mg kg −1 ) in the top 5 cm (Pirani et al, 2006). The soil textural class in the 0‐ to 10‐cm depth interval was confirmed to be silt loam, with 63% silt and 5.5% clay (Pirani, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Research was initiated in 2002 at the Agricultural Research and Extension Center in Fayetteville, AR (36°05′49.18′′ N, 94°10′44.65′′ W; elevation, 394.7 m) (Pirani et al, 2006) in an area mapped as a Captina silt loam (fine‐silty, siliceous, active, mesic Typic Fragiudult) (USDA‐NRCS, 2013). Each of six field plots (6‐m long by 1.5‐m wide) had a 5% west‐to‐east slope, had a history of land‐applied BL before 2002, and was initially chosen based on similar soil pH (6.2 ± 0.5 [SE]) and high Mehlich‐3–extractable P (210 ± 24 mg kg −1 ) in the top 5 cm (Pirani et al, 2006). The soil textural class in the 0‐ to 10‐cm depth interval was confirmed to be silt loam, with 63% silt and 5.5% clay (Pirani, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The lowest amounts of copper and nickel were leached from the NPK treatment, and the lowest quantities of manganese and iron were leached from the control treatment. Pirani et al (2006), who analyzed trace element leaching from poultry litter-amended pastures, reported that reduced application rates of poultry litter did not rapidly decrease the amounts of As, Cd, Se, Cr, Mn, Fe, Ni, Cu, and Zn leached out to subsurface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Animal manures can be soil applied as fresh material or after composting (Moss et al 2002). However, one major concern associated with land application of the above byproducts is the potential for contamination of environment by trace elements and/or pathogens (Gupta and Charles 1999;Jackson et al 2003;Basta et al 2005;Pirani et al 2006) and, in turn, entry of these contaminants into human food chain. With the increased interest of producers and consumers towards the use of organic amendments as substitute for conventional chemical fertilizers, the use of organic amendments in agriculture will increase significantly.…”
Section: Introductionmentioning
confidence: 99%